Laudate Deum: A Framework for Environmental Stewardship and Social Justice in The Philippines and Southeast Asia - Ingles, Antonio Levy S., Jr. (UI Scholars Hub, 2024)
This study explores the intersection of environmental initiatives and social justice movements in the Philippines, a nation rich in biodiversity but acutely vulnerable to climate change and ecological degradation. Using Laudate Deum as a guiding framework, the research examines how the principles of Immediate Action, Collective Responsibility, and Social Justice can inform collaborative strategies to address these challenges. Through an analysis of case studies, this paper highlights the socio-economic impacts of environmental crises, such as deforestation and pollution, and evaluates initiatives like mangrove reforestation and community-based waste management for their ecological and social benefits. The findings reveal that integrating Laudate Deum principles advances synergies between environmental restoration and social equity, emphasizing the need for participatory approaches that empower marginalized communities. This study concludes with actionable recommendations, including strengthening partnerships across sectors, aligning environmental policies with socio-economic needs, and enhancing monitoring frameworks to ensure long-term sustainability. By linking ecological stewardship with social justice, Laudate Deum provides a unifying framework for achieving a just and sustainable future.